The impact of job stress on job performance / Farah Nor Fazlina Nor Azman - Nor Azman, Farah Nor Fazlina
Job performance is one of the crucial part in the organization. This research study has been conducted to examine the impact of job stress on job performance. The independent variables that include in this research study are time pressure, workload, lack of motivation and role conflict. By conducting this research study, researcher will identify whether the independent variables related with the impact of stress in job performance. The questionnaire have been prepared by using google form and will be distribute to the respondent who are related to this research study such as employees in several department at the Sony EMCS Penang. Further, Statistical Package for the Social Sciences (SPSS) version 23 will be used to calculate the data from the questionnaire. In the end, the results will be reveal after all the data successfully collected from the respondent and calculate precisely.